2018
DOI: 10.1016/j.contraception.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous quantitation of multiple contraceptive hormones in human serum by LC–MS/MS

Abstract: This analytical method can be used for quantitating contraceptive steroid levels in women for monitoring systemic exposure to determine drug interactions, nonadherence, misreporting and proper dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…Where indicated, cells collected by vaginal lavage were stained with crystal violet to identify wild-type and NSG mice in the estrus stage of the estrous cycle (26). Also as indicated, mice were euthanized 24 h after the fifth NET-EN treatment, and the serum was sent to the Endocrine Technologies Support Core at the Oregon National Primate Research Center to quantify norethisterone (NET) levels by liquid chromatography-tandem triple quadrupole mass spectrometry (27).…”
Section: Methodsmentioning
confidence: 99%
“…Where indicated, cells collected by vaginal lavage were stained with crystal violet to identify wild-type and NSG mice in the estrus stage of the estrous cycle (26). Also as indicated, mice were euthanized 24 h after the fifth NET-EN treatment, and the serum was sent to the Endocrine Technologies Support Core at the Oregon National Primate Research Center to quantify norethisterone (NET) levels by liquid chromatography-tandem triple quadrupole mass spectrometry (27).…”
Section: Methodsmentioning
confidence: 99%
“…However, Shenouda et al also found that serum immunoassays did not detect estrogen or progesterone in samples from OC users above that observed in men or women in the early follicular phase of the menstrual cycle. Thus, we further recommend that future studies involving OC users should include high-performance liquid chromatography analysis of all analogs of estrogen and progesterone (both endogenous and pharmaceutical), as developed recently (Blue et al, 2018).…”
Section: Limitationsmentioning
confidence: 99%
“…Differences across studies may be impacted by differences in study design, including numbers of women investigated, women's demographic characteristics (ethnicity, race, body mass index, weight and metabolism), number of injections, injection sites, and time and frequency of measurements [14] , [19] . Assay methodologies to measure progestins have evolved over time to be more sensitive and specific; however, this can further complicate interpretation when comparing data from newer and older studies [20] , [21] , [22] . Because of the pharmacokinetics of the formulations, serum concentrations of MPA and NET in the first weeks following injection of DMPA-IM and NET-EN, respectively, exceed contraceptive efficacy but are necessary to ensure maintenance of contraceptive efficacy throughout the dosing duration.…”
Section: Pharmacologic Biologic and Epidemiologic Studies Of Dmpa Anmentioning
confidence: 99%